Multimethod Resolution of a Small‐Scale Case of Commingling1. Issue 2 (16th November 2016) - Finlayson, Janet E.; Bartelink, Eric J.; Perrone, Alexandra; Dalton, Kevin
Abstract: This study highlights the use of multiple methods for resolving a case of commingled human remains. Skeletal remains were located in a marijuana field in rural northern California by law enforcement. Although initially buried in shallow graves, the remains of two decedents were disturbed by large carnivores and scattered over a wide area. The remains were submitted by law enforcement for forensic anthropological analysis and resolution of commingling. To segregate the remains of the two individuals, a number of methods were employed, including: (i) physical matching of fragmented remains; (ii) articulation to evaluate joint congruence; (iii) visual pair‐matching of bilateral elements; (iv) osteometric pair‐matching; (v) evaluation of taphonomic patterns; (vi) DNA analysis; and (vii) portable X‐ray spectrometry (pXRF). This multimethod approach resulted in accurate resolution of the commingling and facilitated reconstruction of the biological profiles, taphonomic patterns, and trauma analysis for each individual.